The yield and biological activity (LC50) of the rotenone extracted from Derris elliptica [compact disc] - 407053 Saiful Irwan Zubairi (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2006